Financial Fraud: A Review of Anomaly Detection Techniques and Recent Advances - Hilal, Waleed; Gadsden, S. Andrew; Yawney, John (Expert systems with applications, 2022)
•This survey includes the most popular and effective anomaly detection techniques.•Highlights recent advancements in semi-supervised and unsupervised learning.•Comprehensive discussion in financial fraud applications.•This survey will form a foundation for future research in the area. With the rise of technology and the continued economic growth evident in modern society, acts of fraud have become much more prevalent in the financial industry, costing institutions and consumers hundreds of billions of dollars annually. Fraudsters are continuously evolving their approaches to exploit the vulnerabilities of the current prevention measures in place, many of whom are targeting the financial sector. These crimes include credit card fraud, healthcare and automobile insurance fraud, money laundering, securities and commodities fraud and insider trading. On their own, fraud prevention systems do not provide adequate security against these criminal acts. As such, the need for fraud detection systems to detect fraudulent acts after they have already been committed and the potential cost savings of doing so is more evident than ever. Anomaly detection techniques have been intensively studied for this purpose by researchers over the last couple of decades, many of which employed statistical, artificial intelligence and machine learning models. Supervised learning algorithms have been the most popular types of models studied in research up until recently. However, supervised learning models are associated with many challenges that have been and can be addressed by semi-supervised and unsupervised learning models proposed in recently published literature. This survey aims to investigate and present a thorough review of the most popular and effective anomaly detection techniques applied to detect financial fraud, with a focus on highlighting the recent advancements in the areas of semi-supervised and unsupervised learning.